(untitled) (Medical Forum Monthly, 2024)
Objective: To know the frequency of HCV, HBV, and Malaria infections in cytopenic patients coming for Bone Marrow Aspiration. Study Duration: Observational study Place and Duration of Study: This study was conducted in Pathology and Medicine Departments of Bacha Khan Medical College Mardan from January 2012 to December 2014. Materials and Methods: 100 patients with cytopenia were referred for Bone Marrow Aspiration and were screened for HBV, HCV and malaria infections. Complete blood counts were performed on 50 healthy individual as a control group. Both Thick and Thin Blood smears were examined for Malaria, while Anti HCV and HBs Ag Screening was done by kit method (Immunochromatographic Method SD company). Complete blood count was performed by Heamatology analyser. ( Sysmex Hematology Analyzer ). Results: 4 out of 100 cytopenic patients were Anti HCV positive, who were referred for Bone Marrow Aspiration. These patients had a Hemoglobin level 10.5 ± 0.978 G/dl, Platelets counts 120± 24.768×103/uL. 2 out of 100 Cytopenic patients were HBs Ag Positive. They had anemia and thrombocytopenia, Hb level was 10.4 ± 0.879 g/dl and platelets count was 119±24.965×103/uL respectively. while 7 (7%) out of 100 cytopenic patients had malaria microscopy. They presented with Hb of 9.5± 0.978 g/dl, platelet count 120± 24.768×103/uL and TLC 3.8 ± 1.365 ×103/uL respectively. Counts in HCV, HBV and malaria are significantly lower than the control groups value < 0.0024. Conclusion: Cytopenia is a significant finding in HCV, HBV and Malaria infections and patients presenting with any cytopenia patients referred for Bone marrow Aspiration presenting with cytopenia should be properly screened for HCV, HBV, and Malaria as these can be the cause of cytopenia thus unnecessary use of Bone Marrow Aspiration can be presented.